A comparative study using an analytical program for the level of effectiveness of the attacking volleyball skill - MUTHANNA JABER, MOHANAD (International Journal of Psychosocial Rehabilitation, 2020)
In light of the statistical treatments of the results that were conducted on the research sample and after presenting, analyzing, and discussing the results, the researcher reached the emergence of moral differences in the level of effectiveness of the skill performance of the attack skill in favor of the teams (Iraq, Lebanon, and Syria) and the absence of moral differences in the level of effectiveness of the performance of the attack skill of the Palestinian team.